(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The effects of carbon fuel consumption on the environment have stimulated development of a ‘net-zero’ energy measurement in buildings envelope for sustainable buildings a net-zero energy is key to reducing energy use and saving money .For several decades, low-income citizens in Moroccan cities have been suffering from thermal inequality, energy poverty and thermal comfort constraints. They resist indoor temperatures of less than 16°C and more than 32°C, , many software come to us from the world to simulate the building envelope . we are working only with software related to: calculation and simulationof electrical and thermal zones, which causes the phenomenon of thermal stress . Among the sources of energy consumption, Heating, Ventilation and air Conditioning (HVAC) systems represent about 50% of the total expenditure in buildings this considerable proportion can be explained in part by the great temperature variations recorded in Morocco, which make it essential to provide air conditioning or heating almost at all times. The development of green buildings thus inevitably requires an optimization of the use of powered mechanical ventilation can increase the airflow and improve heat transfer. Similarly, solar mechanical ventilation can be used to accelerate the heat flow and also using the local building materials p.c.m , with low environmental impact. In this perspective, a clear difference between the use of HVAC systems during the day and at night has been observed. This is because, during the day, the solar irradiation incident on the façade of a building coupled with the various internal gains (occupancy density, lighting, etc.) cause a high demand for air conditioning. This article presents a comparison between the Trnsys and energy plus . If the diversity of these programs is a boon in that it allows many different simulations to be compared, it also poses a problem in terms of comparison of results and even choice of program.